2021
DOI: 10.1186/s13550-021-00825-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex correction improves the accuracy of clinical dopamine transporter imaging

Abstract: Background In clinical diagnostic imaging, dopamine transporter (DAT) SPECT scans are commonly evaluated using automated semiquantitative analysis software. Age correction is routinely implemented, but usually no sex correction of DAT binding is performed. Since there are sex differences in presynaptic dopaminergic function, we investigated the effect of DAT sex correction in a sample of healthy volunteers who underwent brain [123I]-FP-CIT SPECT. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…Studies in healthy subjects have shown that dopamine function is linked to age, sex and season [ 33 , 37 , 38 ]. DVRs in healthy individuals in the bilateral sensorimotor regions of the striatum were found to decrease with age, which is in contrast to busyness-LL in the healthy group, which was not linked to age.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in healthy subjects have shown that dopamine function is linked to age, sex and season [ 33 , 37 , 38 ]. DVRs in healthy individuals in the bilateral sensorimotor regions of the striatum were found to decrease with age, which is in contrast to busyness-LL in the healthy group, which was not linked to age.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that gender can affect presynaptic dopaminergic function. Therefore, strictly speaking, our results provide information only for male ADHD patients ( 53 ). Another limitation of our study design was that no on-drug clinical evaluations were collected to examine the clinical effect of MPH and correlate it with the changes in binding potentials.…”
Section: Discussionmentioning
confidence: 99%
“…HC samples of the FIN cohort were from participants of the previously described PD microbiome follow-up study by Aho et al 13 and HC of the GAMbling and DopAmine Transporter binding (GAMDAT) study. 49…”
Section: Methodsmentioning
confidence: 99%
“…Shotgun metagenomic sequencing would provide complete taxonomy data at the species level and would additionally provide data on the metabolic pathways associated with the sequenced gene fragments. 48,49 Metabolomic analysis would provide actual functional readouts of the gut microbiome. Current data on the metabolome of gut microbiota suggests reduced levels of SCFAs, which would be in line with previous taxonomic studies and our current findings.…”
Section: Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation